In search of the perfect citizen? : the intersection between integration, immigration, and nationality in the EU - Carrera, Sergio (Political scientist) (Immigration and asylum law and policy in Europe, 2009)
Studies the normative intersection between integration, immigration and nationality in the European Union (EU). This book examines the relationship between integration and the legal frameworks of admission, stay and access to nationality by third country nationals at national and European levels.